Pengaruh Pengalaman Kerja, Lingkungan Kerja dan Reward Terhadap Kinerja Karyawan Objek Wisata Pantai Woongrame Desa Kota Pari Pantai Cerrmin Serdang Bedagai - Marissa Tasya Adawiyah; Wan Dian Safina; Toni Hidayat; Muhammad Rahmat (Movere Journal, 2025)
This study aims to determine and analyze the influence of work experience, work environmentand rewards on employee performance. This research is a quantitative study with a descriptiveapproach. The population in this study were all employees of the Woongrame Beach Tourism ObjectManagement. While the sample in this study was the entire population, which was 57 samples. The datacollection technique used was by conducting a survey and distributing questionnaires to respondents.The data analysis technique used was Statistical Data Analysis, Validity Test, Reliability Test, MultipleLinear Regression Analysis, Classical Assumption Test and Hypothesis Test "t" test and F test andDetermination Coefficient Test (R2), which were processed using the SPSS program. The results of thestudy indicate that partially the work experience variable (X1) has a positive and significant effect onthe employee performance variable. The work environment variable (X2) also has a positive andsignificant effect on the employee performance variable. Likewise, the reward variable (X3) has apositive and significant effect on employee performance. While simultaneously it also shows that theindependent variables (Work Experience, Work Environment and Reward) have a positive andsignificant effect on the dependent variable (Employee Performance), with a determination coefficientvalue of 97.6%.